Integrasi Nilai-Nilai Qur’ani dan Hadis dalam Kurikulum Madrasah: Jawaban atas Krisis Moral Siswa Abad 21 - Anita Anita (Yayasan Albahriah Jamiah Indonesia, 2025)
Elementary education in Madrasah Ibtidaiyah faces various challenges in the 21st century, such as rapid technological developments, shifts in cultural values, and low student character. These challenges require an educational approach that focuses not only on cognitive aspects, but also on spiritual and moral aspects. This study aims to analyze the role of the values of the Qur’an and Hadith in responding to the challenges of 21st century elementary education in Madrasah Ibtidaiyah. This study uses a qualitative approach with a literature study method, namely examining relevant primary and secondary sources related to educational values in the Qur’an and Hadith and their application in Madrasah Ibtidaiyah. The results of the study indicate that values such as honesty (ṣidq), responsibility (amanah), tolerance (tasāmuḥ), discipline (intiẓām), and love of knowledge (‘ilm) are important foundations in forming the character of students who are resilient in facing the digital era. In conclusion, internalizing the values of the Qur’an and Hadith into the curriculum and culture of madrasas can be a strategic solution to answer the challenges of 21st century basic education, while also forming a generation that is intellectually, emotionally, and spiritually intelligent.